Cholesterol 25-hydroxylase suppresses avian reovirus replication by its enzymatic product 25-hydroxycholesterol - Wang, Yuyang; Zuo, Wei; Zhang, Yangyang; Bo, Zongyi; Zhang, Chengcheng; Zhang, Xiaorong; Wu, Yantao (Frontiers in Microbiology, 2023)
Avian reovirus (ARV) causing viral arthritis/tenosynovitis and viral enteritis in domestic fowl has significantly threatened on the poultry industry worldwide. ARV is a non-enveloped fusogenic virus that belongs to the Reoviridae family. Previous research revealed that cellular cholesterol in lipid rafts is essential for ARV replication. It has been reported that cholesterol 25-hydroxylase (CH25H) and its product 25-hydroxycholesterol (25HC) have antiviral activities against enveloped viruses. However, few studies characterized the association of non-enveloped viruses with CH25H and the role of CH25H in the regulation of ARV replication. In this study, the expression of chicken CH25H (chCH25H) was found to be upregulated in ARV-infected cells at the early stage of infection. The results of overexpression and knockdown assays revealed that chCH25H has a significant antiviral effect against ARV infection. Furthermore, a 25HC treatment significantly inhibited ARV replication in a dose-dependent manner at both the entry and post-entry stages, and a chCH25H mutant lacking hydroxylase activity failed to inhibit ARV infection. These results indicate that CH25H, depending on its enzyme activity, exerts the antiviral effect against ARV via the synthesis of 25HC. In addition, we revealed that 25HC produced by CH25H inhibits viral entry by delaying the kinetics of ARV uncoating, and CH25H blocks cell-cell membrane fusion induced by the p10 protein of ARV. Altogether, our findings showed that CH25H, as a natural host restriction factor, possessed antiviral activity against ARV targeting viral entry and syncytium formation, through an enzyme activity-dependent way. This study may provide new insights into the development of broad-spectrum antiviral therapies.